An Implicit System for Predicting Interests - White, Ryen W.; Jose, Joemon M. (27th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2004), Sheffield, United Kingdom, 2004)
We demonstrate an adaptive search system that works proactively to help searchers find relevant information. The system observes searcher interaction, uses what it sees to model information needs and chooses additional query terms. The system watches for changes in the topic of the search and selects retrieval strategies that reflect the extent to which the topic is seen to change.